Qualitative study about pedagogical practices and social inclusion strategies in Uruguayan schools - Rodríguez Zidán, Eduardo; Vázquez Clavera, María Inés (Avances en Supervisión Educativa, 2016)
The following report presents some of the results of an investigation held in Uruguay aimed at providing knowledge about pedagogical practices and professional skills of teachers working in public primary schools located in high vulnerability social contexts.The universe of the study is composed by ten schools of Programa APRENDER. The consulted main actors are the early-career and expert teachers who develop their practice in these schools. From an approach that combined qualitative techniques, twenty-two in-depth interviews, field records and institutional documents are analyzed.The focus or research problem is to analyze and understand not only the significances given by early-career and expert teachers to professional skills but also other aspects associated with their representations about educational practices in socially inclusive schools.The document describes and categorizes these significances based on semantic relations and domain analysis. Due to the findings discussion, suggestions of some changes in educational policies are provided as well as recommendations for supervisors and managers of social inclusion programs.
Keywords: educational practices; professional skills; early-career and expert teachers; socially inclusive education